CONVERTERE AS THE CHRISTIAN IDEOLOGY: A Study of Biblical Perspectives on Religious Conversion - Kalluveettil, Paul (Journal of Dharma, 2020)
The controversial issue of religious conversion divides the Indians for or against it. Some stand for the fundamental right of every human being to choose his or her religion, and the freedom to leave the present faith in favour of another one. Usually, Christians ascribe to this position. Hindu fundamentalists militate against every kind of religious conversion, either by coercion, remuneration or out of one’s conviction. The ideology behind the anti-conversion bills seems to be this Hindutva preoccupation. Christian missionaries are the targets of the present systematic and subtle propaganda war. In some other countries, which enjoy an Islam majority, the Muslims fight tooth and nail against conversion to Christianity. Perhaps the intolerant attitudes and wrong missionary approaches of Christians would have played a part in this anti-Christian wave among the populace of India. The pitiable fact behind this vicious atmosphere is that both Christians and non-Christians have misunderstood and/or misrepresented the biblical perspectives and Jesus’ vision on conversion. Hence, this study is devoted to unearth the biblical foundations and ideals concerning this theme.